2020
DOI: 10.1021/acssensors.0c00863
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Ultrafast Humidity Sensor Based on Microknot Resonator-Assisted Mach–Zehnder for Monitoring Human Breath

Abstract: Monitoring the dynamic humidity requires sensors with fast response and anti-electromagnetic interference, especially for human respiration. Here, an ultrafast fiber-optic breath sensor based on the humidity-sensitive characteristics of gelatin film is proposed and experimentally demonstrated. The sensor consists of a microknot resonator superimposed on a Mach−Zehnder (MZ) interferometer produced by a tapered single-mode fiber, which has an ultrafast response (84 ms) and recovery time (29 ms) and a large dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Unlike their electronic counterparts, these sensors are unaffected by electromagnetic interference because the sensing components do not include electronic circuits [ 75 , 76 ]. Thus, they can be used as breathing monitors [ 77 , 78 ], ventilators, and other respiratory aids [ 79 , 80 , 81 , 82 ] for human patients in environments producing strong electromagnetic fields such as inside an MRI chamber. In addition, they are compact and lightweight, making them portable.…”
Section: Types Of Fast-response Humidity Sensormentioning
confidence: 99%
“…Unlike their electronic counterparts, these sensors are unaffected by electromagnetic interference because the sensing components do not include electronic circuits [ 75 , 76 ]. Thus, they can be used as breathing monitors [ 77 , 78 ], ventilators, and other respiratory aids [ 79 , 80 , 81 , 82 ] for human patients in environments producing strong electromagnetic fields such as inside an MRI chamber. In addition, they are compact and lightweight, making them portable.…”
Section: Types Of Fast-response Humidity Sensormentioning
confidence: 99%
“…Similarly, Yi et al have reported a fiber optic humidity sensor with a biocompatible transducer made from gelatin they claimed exhibits superior response and recovery times to previous work. [20] They showed that the gelatin's refractive index is dependent upon humidity and demonstrated its efficacy as a breath humidity sensor, drawing conclusions that it could be used for food processing.…”
Section: Figure 2 A)mentioning
confidence: 99%
“…For instance, using a humidity sensor to detect the breathing state and reflect the vital characteristics of the human body is of great significance to clinical medicine. 3,4 Besides, exploiting humidity sensors to evaluate the waxing of fruits can bring high economic benefits to agriculture. 5 Generally, the humidity changes during breathing are large, and the humidity changes in the environment are small.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of modern industrial, smart agricultural, and intelligent home automation, the detection and control of humidity have become an essential link in our daily life. , Real-time and accurate monitoring of the change in relative humidity (RH) has huge application prospects. For instance, using a humidity sensor to detect the breathing state and reflect the vital characteristics of the human body is of great significance to clinical medicine. , Besides, exploiting humidity sensors to evaluate the waxing of fruits can bring high economic benefits to agriculture . Generally, the humidity changes during breathing are large, and the humidity changes in the environment are small.…”
Section: Introductionmentioning
confidence: 99%